1991
DOI: 10.1177/070674379103600706
|View full text |Cite
|
Sign up to set email alerts
|

Homebound Aged: The Dilemma of Psychiatric Intervention

Abstract: This study reports the 12 month experience of a hospital-based, multidisciplinary psychogeriatric community team. The patients evaluated were unable to come to the hospital clinics because of a psychiatric and/or physical disability. The group included some patients rarely seen in psychiatric office practice and outpatient facilities, but who posed problems for their families and the community. Some required referral to a clinic, crisis management or emergency hospitalization. Others however, required only min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…All community‐based studies that made age comparisons found the home‐bound significantly older than the non‐homebound. In the reports restricted to beneficiaries of various outreach programs 1–4,6,7,9,10 , in which there was no non‐homebound group for comparison, the mean age of the homebound ranged from 75 to 85 years. The socioeconomic status of the homebound was also relatively low: in the New Haven 16 and Chicago 13 samples, as in the Monongahela Valley, the home‐bound were less educated than the non‐homebound, and in New Haven 16 and Kentucky, 14 they had lower household incomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All community‐based studies that made age comparisons found the home‐bound significantly older than the non‐homebound. In the reports restricted to beneficiaries of various outreach programs 1–4,6,7,9,10 , in which there was no non‐homebound group for comparison, the mean age of the homebound ranged from 75 to 85 years. The socioeconomic status of the homebound was also relatively low: in the New Haven 16 and Chicago 13 samples, as in the Monongahela Valley, the home‐bound were less educated than the non‐homebound, and in New Haven 16 and Kentucky, 14 they had lower household incomes.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively high rates of cognitive dysfunction and/or psychiatric problems (dementia, depression, paranoia) were found among patients served by outreach programs for homebound older adults 1–4,6–10,13 . Such rates appear to reflect the basis upon which these individuals were referred to the outreach services, although Reifler et al 9 found that reasons for referral often did not predict subsequent diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its potential advantages, implementation of a quality home psychiatric treatment program is not feasible in many states because of: It is to be hoped that further research demonstrating the efficacy of psychiatric home care programs will support a reconsideration of these policies. A number of demonstration projects (Levy, 1985;Ratina, 1982;Parish & Landsberg, 1984;Morgan & Wieman, 1990;Sherr, Eskridge, & Lewis, 1976;Selan & Gold, 1980;Currie, Moore, Friedman, & Warshaw, 1981;Reifler, Raskind, & Kethley, 1982;Brown & Lieff, 1982;Wasson, Ripeckyj, Lazarus, Kupferer, Barry, & Force, 1984;Raschko, 1988;Roca, Storer, Robbins, Tlasek, & Rabins, 1990;DeRenzo, Byer, Grady, Matricardi, Lehmann, & Gradet, 1991;Grauer, Kravitz, Davis, & Rodrigue, 1991;Holroyd, Baukhages-Smith, & Rabins, 1991;Kohn, Goldsmith, & Sedgwick, in press) have touted the benefits of in-home psychiatric treatment for geriatric patients. Unfortunately, no research has been conducted in the United States to demonstrate whether such a treatment approach is more effective and economical than traditional models.…”
Section: Discussionmentioning
confidence: 99%